2023
DOI: 10.1097/prs.0000000000010507
|View full text |Cite
|
Sign up to set email alerts
|

Novel Clinical Anatomic Consideration of the Superficial and Deep Layers of the Deep Temporal Fascia

Abstract: he deep temporal fascia (DTF) is a dense aponeurotic layer that covers the temporalis muscle, which is found on the lateral side of the head. 1 It originates from the superior temporal line and descends as a single layer. Approximately at the level of the superior orbital rim, the DTF is divided into superficial and deep layers reaching the lateral and medial borders of the upper surface of the zygomatic arch, respectively. 1,2 Clinically, the DTF provides anchoring during thread lifting, which is a minimally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Interestingly, a cadaver study illustrated that, when supine, the areas anterior to the ears and along the jawline exhibit increased tautness and definition, avoiding the accumulation of loose tissues that could otherwise create a bulging appearance along the lower facial contours (Figure 4). 25–27 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a cadaver study illustrated that, when supine, the areas anterior to the ears and along the jawline exhibit increased tautness and definition, avoiding the accumulation of loose tissues that could otherwise create a bulging appearance along the lower facial contours (Figure 4). 25–27 …”
Section: Introductionmentioning
confidence: 99%
“…In a morphometrical and histological study, Morales-Avalos et al [ 6 ] demonstrated the advantages of the DLTF for graft use in terms of its fiber arrangement. Surprisingly, in living humans, an excellent ultrasound technique is able to demonstrate details of the multilaminar STFL and its individual variation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%